Prudenzio e il martirio DI Eulalia: una rilettura del Peristephanon 3 - Guttilla, Giuseppe (Revue d'études augustiniennes et patristiques, 2008)
Prudentius’ perist. 3 (Hymnus in honorem passionis Eulaliae, beatissimae martyris) points out in a clear way a mélange of different literary genres. Its initial lines have a consolatory content that goes back to Jerome’s Epitaphium Paulae (epist. 108) and to Paulinus of Nola’s carm. 31. The lines that introduce Eulalia’s passio follow in a remarkable way Paulinus’ natalicia III, IV, and VI (carm. 14, 15, and 18). On the contrary, we cannot determine with certainty which sources Prudentius really uses in its main part. If we consider their content, the final lines (186-215) once more show their evident dependence on that part of natalicia above mentioned, where Paulinus celebrates the anniversary of saint Felix’s death and his ascent to Heaven.